Annotated checklist of aquatic beetles (Coleoptera) and true bugs (Heteroptera) in the Azores Islands: new records and corrections of colonization status - Lamelas-López, Lucas; Raposeiro, Pedro Miguel; Borges, Paulo A. V.; Florencio, Margarita (Zootaxa, 2017)
In comparison with other Macaronesian archipelagos, Azorean freshwater macroinvertebrates are characterized by a smaller list of species at the archipelago regional scale. Although knowledge of the freshwater fauna of the Azores has improved in recent years through the implementation of the "Water Framework Directive", we are still far from having a complete inventory and even further from knowing the precise distribution and biology of each species. The lack of knowledge about Azorean freshwater species is coupled with the vulnerability of their habitats to anthropogenic disturbances and the introduction of non-native species. In contributing to overcome Wallacean and Hutchinsonian biodiversity shortfalls, we here provide expanded knowledge on the distribution and biology of the freshwater species of Coleoptera and Heteroptera in the Azores. We compile data from various fieldwork performed between 2006 and 2014, encompassing four islands in the archipelago. We detected new records of two aquatic Heteroptera species (belonging to the families Corixidae and Notonectidae) and six of aquatic Coleoptera (belonging to the families Dytiscidae, Gyrinidae, Hydrophilidae and Hydraenidae) in these islands, and also a new record (Enochrus fuscipennis) for the Azorean archipelago. We also suggest that the introduced colonization status of three Coleoptera species of the family Hydrophilidae should be reformulated as possibly native, with implications for conservation.